Hybrid Eulerian-Lagrangian method for soot modelling applied to ethylene-air premixed flames. (1st March 2020) - Dellinger, Nicolas; Bertier, Nicolas; Dupoirieux, Francis; Legros, Guillaume
Abstract: Soot formation has become an important issue in the design of gas turbine combustors due to its environmental impact and its contribution to radiative heat transfer in the combustion chamber. However, efficient and accurate prediction of soot particles formation, growth, oxidation and interaction in gas turbine combustors is still an open field in computational fluid dynamics. The present approach proposes to combine a reduced gas-phase chemistry, a sectional model for polycyclic aromatic hydrocarbons, and a Lagrangian description of soot particles dynamics. The Lagrangian description has been chosen for its ability to simulate the evolution of the particle size distribution. A numerical procedure is proposed to minimise its CPU cost. This approach was successfully applied to the simulation of steady laminar premixed ethylene-air flames at three fuel equivalence ratios, which constitutes a prerequisite towards its use in an aeronautical combustion chamber. Highlights: Soot particles dynamics is described through a detailed Lagrangian tracking method. Soot particles growth and oxidation processes are taken into account. Soot particles interactions are limited with success to coalescence as a first guess. Particle size distributions are extracted efficiently through population reduction. Targeted flames for validation are laminar premixed ethylene-air flames.